The cell wall and the response and tolerance to stresses of biotechnological relevance in yeasts - Ribeiro, Ricardo A.; Bourbon-Melo, Nuno; Sá-Correia, Isabel (Frontiers in Microbiology, 2022)
In industrial settings and processes, yeasts may face multiple adverse environmental conditions. These include exposure to non-optimal temperatures or pH, osmotic stress and deleterious concentrations of diverse inhibitory compounds. These toxic chemicals may result from the desired accumulation of added-value bio-products, yeast metabolism, or be present or derive from the pre-treatment of feedstocks, as in lignocellulosic biomass hydrolysates. Adaptation and tolerance to industrially relevant stress factors involves highly complex and coordinated molecular mechanisms occurring in the yeast cell with repercussions on the performance and economy of bioprocesses, or on the microbiological stability and conservation of foods, beverages and other goods. To sense, survive, and adapt to different stresses, yeasts rely on a network of signalling pathways to modulate the global transcriptional response and elicit coordinated changes in the cell. In particular, these pathways cooperate and tightly regulate the composition, organisation and biophysical properties of the cell wall. The intricacy of the underlying regulatory networks reflects the major role of the cell wall as the first line of defence against a wide range of environmental stresses. However, the involvement of cell wall in the adaptation and tolerance of yeasts to multiple stresses of biotechnological relevance has not received the deserved attention. This article provides an overview of the molecular mechanisms involved in fine-tuning cell wall physicochemical properties during the stress response of Saccharomyces cerevisiae and their implication in stress tolerance. The available information for non-conventional yeast species is also included. These non-Saccharomyces species have recently been on the focus of very active research to better explore or control their biotechnological potential envisaging the transition to a sustainable circular bioeconomy.